2012
DOI: 10.1242/dev.085936
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulatory networks in epiblast cells and during anterior neural plate development as modeled in epiblast stem cells

Abstract: Somatic development initiates from the epiblast in post-implantation mammalian embryos. Recent establishment of epiblast stem cell (EpiSC) lines has opened up new avenues of investigation of the mechanisms that regulate the epiblast state and initiate lineage-specific somatic development. Here, we investigated the role of cell-intrinsic core transcriptional regulation in the epiblast and during derivation of the anterior neural plate (ANP) using a mouse EpiSC model. Cells that developed from EpiSCs in one day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 65 publications
4
111
0
Order By: Relevance
“…Studies in mouse EpiSCs and human embryonic stem cells (ESCs) also revealed that inhibition of Nodal signaling by SB431542 (Inman et al, 2002;Laping et al, 2002) attenuates mesoderm/endoderm differentiation and promotes neural induction (Chng et al, 2010;Patani et al, 2009;Vallier et al, 2009). A recent study further revealed that cells developing from EpiSCs in the absence of extrinsic signals (including Nodal signaling) express levels of core transcription factors similar to the anterior neural plate of ~E7.5 embryos (Iwafuchi-Doi et al, 2012). We show here that Nodal inhibition is not merely an enhancer of neural fate.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Studies in mouse EpiSCs and human embryonic stem cells (ESCs) also revealed that inhibition of Nodal signaling by SB431542 (Inman et al, 2002;Laping et al, 2002) attenuates mesoderm/endoderm differentiation and promotes neural induction (Chng et al, 2010;Patani et al, 2009;Vallier et al, 2009). A recent study further revealed that cells developing from EpiSCs in the absence of extrinsic signals (including Nodal signaling) express levels of core transcription factors similar to the anterior neural plate of ~E7.5 embryos (Iwafuchi-Doi et al, 2012). We show here that Nodal inhibition is not merely an enhancer of neural fate.…”
mentioning
confidence: 50%
“…Epiblast cells from Nodal −/− embryos readily differentiate into neurons in explant culture (Camus et al, 2006). Studies in mouse EpiSCs and human ESCs also revealed that inhibition of Nodal signaling promotes neural induction (Chng et al, 2010;Iwafuchi-Doi et al, 2012;Patani et al, 2009;Vallier et al, 2009).…”
Section: Research Articlementioning
confidence: 99%
“…Chimera experiments have shown that OTX2 acts cellautonomously to maintain the expression of the anterior neuronal markers Hesx1, Wnt1, Cdh4 and Efna2 in the ANE (Rhinn et al, 1999), whereas inactivating Otx2 in epiblast stem cells impairs the differentiation of anterior neural tissues (Iwafuchi-Doi et al, 2012;Acampora et al, 2013). These results highlight the intrinsic requirement of Otx2 activity in the ANE for differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse, neural stem cells prepared from the whole cerebrum of E14 embryos were found to express Pou5f1, although at low levels [42]. Expression of Pou5f1 was also detected by qRT-PCR in early populations of Sox1-expressing neural plate cells derived from epiblast stem cells [43]. Recently, the coexpression of pluripotent and early neuronal markers (POU5F1 and PAX6) in lineageprimed human ESCs was confirmed by single-cell qRT-PCR [11].…”
Section: Discussionmentioning
confidence: 93%